Eradicating chancroid - Steen Richard (The World Health Organization, 2001)
Genital ulcers are important cofactors of HIV transmission in the countries most severely affected by HIV/ AIDS. Chancroid is a common cause of genital ulcer in all 18 countries where adult HIV prevalence surpasses 8% and is rare in countries with low-level HIV epidemics. Haemophilus ducreyi, the causative organism of chancroid, is biologically vulnerable and occupies a precarious epidemiological niche. Both simple, topical hygiene and male circumcision greatly reduce risk of infection and several classes of antibiotics - some of which can be administered in single-dose treatment regimens - provide rapid cure. H. ducreyi depends on sexual networks with high rates of partner change for its survival, thriving in environments characterized by male mobility and intensive commercial sex activity. Elimination of H. ducreyi infection from vulnerable groups results in disappearance of chancroid from the larger community. Once endemic in Europe and North America, chancroid began a steady decline early in the twentieth century, well before the discovery of antibiotics. Social changes - resulting in changing patterns of commercial sex - probably disrupted the conditions needed to sustain chancroid as an endemic disease. Sporadic outbreaks are now easily controlled when effective curative and preventive services are made available to sex workers and their clients. More recently, chancroid prevalence has declined markedly in countries such as the Philippines, Senegal, and Thailand, a development that may contribute to stabilization of the HIV epidemics in these countries. Eradication of chancroid is a feasible public health objective. Protecting sex workers and their clients from exposure to sexually transmitted diseases (STDs) and improving curative services for STDs are among the proven strategies that could be employed.